Reducing stigma in reproductive health. Issue 1 (21st January 2014) - Cook, Rebecca J.; Dickens, Bernard M.
Abstract: Stigmatization marks individuals for disgrace, shame, and even disgust—spoiling or tarnishing their social identities. It can be imposed accidentally by thoughtlessness or insensitivity; incidentally to another purpose; or deliberately to deter or punish conduct considered harmful to actors themselves, others, society, or moral values. Stigma has permeated attitudes toward recipients of sexual and reproductive health services, and at times to service providers. Resort to contraceptive products, to voluntary sterilization and abortion, and now to medically assisted reproductive care to overcome infertility has attracted stigma. Unmarried motherhood has a long history of shame, projected onto the "illegitimate" (bastard) child. The stigma of contracting sexually transmitted infections has been reinvigorated with HIV infection. Gynecologists and their professional associations, ethically committed to uphold human dignity and equality, especially for vulnerable women for whom they care, should be active to guard against, counteract, and relieve stigmatization of their patients and of related service providers.